Recurrence characteristics and clinicopathological results of borderline ovarian tumors - Lina Niu; Huihui Tian; Yongjun Xu; Jieqiong Cao; Xu Zhang; Junli Zhang; Jiajia Hou; Weiqin Lv; Junxia Wang; Li Xin; XuFeng Dong; Tao Xu; et al. (BMC Women's Health, 2021)
Abstract Background This study aimed to investigate the clinical and pathological characteristics, and the recurrence and prognostic factors of borderline ovarian tumors (BOTs). Methods The data of 286 patients admitted to hospital and followed up for more than ten months were analyzed retrospectively to study the clinicopathological characteristics and related factors of recurrence. Results The median age of the patients was 42.06 ± 14.97 years, and the duration of the follow-up ranged from 10–109 months. During the follow-up period, 40 patients had a recurrence. Of these patients, 36 were ≤ 40 years, and patients with premenopausal recurrence accounted for 20.5% (36/176). In patients undergoing conservative treatment or radical operations, the recurrence rates were 21.3% and 1.8%, respectively, and they were 13.4% (36/268) in patients at Federation International of Gynecology and Obstetrics (FIGO) stage I, and 22.2% (4/18) in patients at an advanced stage. Postoperative pathology revealed that 40 patients had micropapillary tumors, among whom ten patients (25%) had a recurrence, and 19 patients had complications with interstitial infiltration. Of these 19 patients, six had a recurrence (31.5%). Another 22 patients had complications with calcified sand bodies; among these, eight patients (36.4%) had a recurrence. All the differences were statistically significant (P < 0.05). There were four cancer-related deaths during the follow-up period. Late FIGO stage, conservative operation, and a high level of carbohydrate antigen 125 (CA125) were independent risk factors for the recurrence of BOTs. Conclusion BOTs usually occur in women under 40 years, have an occult onset, and half of the patients have no obvious clinical manifestations. Serum CA125 level can be used as a tumor marker to detect BOTs and the risk of its recurrence. Operation mode and FIGO stage are important independent factors for the recurrence of BOTs.